Ligand effects on the surface composition of Rh-containing ionic liquid solutions used in hydroformylation catalysis - Kolbeck, Claudia; Paape, Natalia; Cremer, Till; Schulz, Peter; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (Chemistry - A European Journal, 2010)
The chemical surface composition of Rh-containing ionic liquid solutions has been studied by angle-resolved X-ray photoelectron spectroscopy (ARXPS). Rh-tppts complexes of high relevance for multiphase hydroformylation catalysis showed remarkable surface activity, whereas non-tppts containing systems showed Rh depleting from the surface (tppts=tris(3-sodium sulfonatophenyl)phosphine). © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.